OPTIMALISASI LAHAN KURANG PRODUKTIF DALAM RANGKA MENDUKUNG KETAHANAN PANGAN MELALUI PEMBERDAYAAN MASYARAKAT KOTA - Jajuk Herawati; Dwie Retna Suryaningsih; M. Thohiron; Ken William; Habib Habib (Yayasan Education and Social Center, 2023)
The Faculty of Agriculture, Wijaya Kusuma University, Surabaya has established an ongoing partnership through the Community Service Program where one of the fostered partners is the